Optimasi Produksi Barang Menggunakan Logika Fuzzy Metode Mamdani - Nasution, Vani Maharani; Prakarsa, Graha (STMIK Budi Darma, 2020)
Maximum profit gained from maximum sales. Maximum sales means that they can meet the demands. If the products produced by the company is less than requests then the company will lose the opportunity to get maximum profit. Therefore, planning the Amount products in a company is very important in order to meet the market demand precisely and with the appropriate amount. Factors that need to be considered in determining the amount products, such as the demand and supply of old periods. The availability of production goods is still difficult to monitor by the company, because the system is still relying on manual calculations of the company employees, to assist the company in predicting the availability of production goods Effective then used the fuzzy logic calculations. During this time the availability of production goods in Salman Collection is seen from customer request. This makes the company not get the maximum profit because there is no planning the amount of production of goods. This study uses methods with a descriptive approach using the fuzzy logic Mamdani technique. The results of this research is an application of calculation of goods production based on the fuzzy manual calculations of the